Optimal Three-Dimensional Correction of Idiopathic Scoliosis - Kotwicki, T.; Marciniak, W. (Engineering Transactions, 2001)
We have reviewed the standing position antero-posterior and lateral radiographs of 64 children operated on for juvenile or adolescent idiopathic scoliosis. Twenty five patients had Cotrel-Dubousset posterior instrumentation, twenty one were corrected with Pouliquen anterior plate and twenty one with Harrington distraction rod. The transversal plane of the spine was visualised by computer reconstruction using sonic digitizer GP-9 and the programme Rachis. The following parameters were compared : Cobb angle, Perdriolle angle of vertebral rotation, apical vertebra transposition. Transversal plane reconstruction images were also compared. The results showed better 3-D correction in Cotrel-Dubousset technique over the Harrington technique. This concerned Cobb angle and apical vertebra transposition but not the vertebral rotation. The anterior instrumentation gave the best correction in each of the three planes. In particular, the vertebral rotation was significantly diminished with anterior technique. The results were also confirmed by computer reconstruction of the transversal plane of the spine. The authors conclude that vertebral derotation can hardly be achieved with posterior spinal techniques, regardless of the type of instrumentation applied. Following the biomechanical analysis of the spatial displacement of each vertebra of the scoliotic curve after operation, a complex movement of the corrected spine can be evaluated.